The Complexity of Premature Coronary Artery Disease - Noverike, Nikhen; Rahimah, Anna Fuji; Rohman, Mohammad Saifur (Heart Science Journal, 2024)
Premature Coronary Artery Disease presents a significant health concern globally, characterized by the onset of coronary atherosclerosis at an early age, typically before the age of 55 in men and 65 in women. This review provides a comprehensive examination of the various aspects of premature CAD, ranging from its underlying pathophysiology to diagnostic modalities such as coronary angiography. Beginning with an overview of the risk factors contributing to premature CAD, including genetic predispositions, lifestyle factors, and metabolic disorders, the review delves into the intricate mechanisms involved in the initiation and progression of atherosclerosis. Furthermore, the review discusses the clinical manifestations and challenges associated with diagnosing premature CAD, particularly in asymptomatic individuals. It examines the utility of non-invasive imaging techniques, stress testing in identifying coronary artery stenosis, cardiovascular risk and the principles of coronary angiography. The review outlines the principles of coronary angiography, including patient preparation, procedural techniques, and interpretation of angiographic findings. In conclusion, this comprehensive review provides insights into the multifaceted nature of premature CAD, elucidating its pathogenesis, clinical presentation, and diagnostic evaluation, with a focus on the pivotal role of coronary angiography in guiding therapeutic interventions and optimizing patient outcomes.